The story you need to tell : writing to heal from trauma, illness, or loss - Marinella, Sandra, 1950- (New World Library, 2017)
"Informed by the author's pioneering work with veterans and cancer patients, and her years of teaching writing and researching its healing properties, The Story You Need to Tell is a practical and inspiring guide to transformational personal storytelling. Riveting true stories illustrate Marinella's methods for understanding, telling, and editing our own stories in ways that foster resilience and renewal. Marinella also shares her own experience of using journal and expressive writing to navigate challenges including breast cancer and post-partum depression. Each of the techniques, prompts, and exercises she presents work to "unravel the knot inside and to make sense of loss." Based on a profound understanding of how "in our sadness and pain we can be remade," this is the kind of storytelling - and the kind of book - that can change and perhaps even save a life"--